2006
DOI: 10.1111/j.1572-0241.2006.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection Frequency and Risk of Celiac Disease Autoimmunity in Early Childhood: A Longitudinal Study

Abstract: This prospective study provides the first indication that a high frequency of rotavirus infections may increase the risk of celiac disease autoimmunity in childhood in genetically predisposed individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
323
2
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(345 citation statements)
references
References 28 publications
4
323
2
16
Order By: Relevance
“…[7,8] Significant interest in rotavirus as a possible infectious trigger was generated following a study by Stene et al showing that frequent rotavirus infections increased the risk of CD development in 54 cases of children under four years of age. [9] Additional case reports of CD development in children following rotavirus infection have been published. Of recent interest are the roles of IL-15 and gastrointestinal flora in the proximal small bowel in relation to precipitating disease.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…[7,8] Significant interest in rotavirus as a possible infectious trigger was generated following a study by Stene et al showing that frequent rotavirus infections increased the risk of CD development in 54 cases of children under four years of age. [9] Additional case reports of CD development in children following rotavirus infection have been published. Of recent interest are the roles of IL-15 and gastrointestinal flora in the proximal small bowel in relation to precipitating disease.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…A prospective study in children genetically predisposed to CD showed that the high frequency of rotavirus infections increased the risk of developing the disease. 14 Also a role was recently established for reovirus in the loss of gluten tolerance. 15 In the case of bacterial pathogens causing gastrointestinal infections, the development of CD was linked to previous Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…20 Differences in infections in early life may also be relevant. For example, in one study, 21 rotavirus infection was implicated in the development of celiac disease, a finding that requires investigation in future studies. Our findings indicate the need for study of the complex relationships among genetic, environmental, and gestational factors that may play a role in the development of celiac disease in early childhood.…”
Section: Discussionmentioning
confidence: 99%